Paper pulp molded product for food packaging and preparation method and pulp of paper pulp molded product
By adding nanocellulose and waterproofing agents to pulp molded products and combining them with specific processes to form a dense network structure, the performance deficiencies of traditional pulp molded products are solved, resulting in high-performance, environmentally friendly, and biodegradable food packaging materials.
Patent Information
- Application Number
- CN202511648342.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-11
- Publication Date
- 2026-01-27
AI Technical Summary
Traditional pulp molding products suffer from poor barrier properties, insufficient mechanical strength, and weak moisture resistance, making it difficult to meet the requirements of high-end food packaging. At the same time, existing improvement methods often sacrifice the environmental friendliness or economy of the materials.
By adding nanocellulose and waterproofing agents to plant fiber pulp, a dense network structure is formed through vacuum adsorption molding and multi-stage hot pressing and drying processes, which improves barrier properties and mechanical strength while maintaining biodegradability.
It significantly reduces porosity, improves barrier properties, mechanical strength, and moisture resistance, ensuring the product's environmental advantages, and possesses industrial feasibility and cost-effectiveness.
Smart Images

Figure CN121407446A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of papermaking, specifically to a pulp molded product for food packaging, its preparation method, and the pulp. Background Technology
[0002] With the increasing global awareness of environmental protection and the deepening of sustainable development strategies, the food packaging industry is undergoing an industrial transformation centered on green, environmentally friendly, and biodegradable materials. Among many environmentally friendly materials, pulp molded products, due to their wide availability of raw materials, biodegradability, and recyclability, have become one of the key materials to replace traditional plastic packaging and are widely used in food trays, lunch boxes, cushioning liners, and other fields. However, as is known to those skilled in the art, traditional pulp molded products are mainly produced through processes such as hydraulic pulping, vacuum adsorption molding, and hot pressing and drying. In this process, pulp fibers are randomly interwoven and piled up, inevitably forming a large number of micro and macro pores between the fibers. This inherent porous structure leads to the following significant defects in traditional pulp molded products: 1. Poor barrier performance: The high porosity allows gases such as oxygen and water vapor to easily permeate, resulting in insufficient protection for contents (such as oily foods and water-containing foods), making it difficult to meet the stringent shelf-life requirements of high-end food packaging. 2. Insufficient mechanical strength: The porous structure reduces the effective load-bearing area of the material, resulting in lower key mechanical properties such as tensile strength, burst strength, and stiffness. This makes it prone to deformation or damage during transportation, stacking, and even use. 3. Weak moisture resistance: The porous structure is hydrophilic, easily absorbing moisture from the environment, causing the packaging box to soften and lose strength, severely affecting its performance.
[0003] To improve these properties, existing technologies have proposed several solutions. For example, one approach is to increase the beating degree or hot-pressing pressure to enhance the bonding tightness between fibers, thereby reducing porosity. However, this method has limitations: excessively high beating degrees can lead to difficulties in pulp filtration, affecting molding efficiency; while excessive pressure may crush the fiber structure and even cause product damage. Another common approach is to add waterproofing agents, reinforcing agents (such as sizing agents and dry strength agents) to the pulp, or directly coat / apply a barrier layer (such as PE film or PLA coating) to the molded surface. However, adding chemical additives may introduce non-environmentally friendly substances, contradicting the "fully degradable" intention of pulp molding; while the coating process increases the difficulty of material separation and recycling and raises production costs. Therefore, a prominent contradiction exists in existing technologies: on the one hand, the market urgently needs high-performance pulp molding packaging to replace plastics; on the other hand, existing technologies for improving porosity are either limited in effectiveness or come at the cost of sacrificing the environmental friendliness, economy, or degradability of the material. Summary of the Invention
[0004] The first aspect of this application provides a pulp for molded pulp articles for food packaging, the pulp comprising: 85-95 parts by weight of plant fiber pulp, 5-15 parts by weight of nanocellulose, and 3-7 parts by weight of waterproofing agent.
[0005] In some alternative embodiments, the nanocellulose includes any one or a combination of two of cellulose nanofibers and cellulose nanocrystals.
[0006] In some optional embodiments, the nanocellulose has an average diameter of 5-100 nm and an average length of 0.1-10 μm.
[0007] In some alternative embodiments, the waterproofing agent comprises any one or a combination of multiple of alkyl ketene dimers, alkenyl succinic anhydride, and paraffin emulsions.
[0008] In some optional embodiments, the nanocellulose includes cellulose nanofibers and cellulose nanocrystals, wherein the cellulose nanofibers have a diameter of 10-50 nm and a length of 1-5 μm; and the cellulose nanocrystals have a diameter of 5-30 nm and a length of 0.1-0.5 μm.
[0009] Secondly, embodiments of this application provide a method for preparing pulp molded articles for food packaging, the method comprising: Prepare a slurry, wherein the slurry is the slurry described in the above embodiments; Vacuum adsorption molding; Hot pressing, drying, and shaping.
[0010] In some optional embodiments, the step of preparing the slurry includes: Plant fiber pulp boards are decomposed in water to prepare a uniform primary pulp with a concentration of 1-5 wt%. Under high-speed shearing, nanocellulose was added to deionized water to prepare a stable suspension of 0.5-1.0 wt%, and the suspension was then subjected to ultrasonic treatment. The nanocellulose suspension was added to the primary plant fiber pulp and stirred to obtain the secondary pulp; The emulsified waterproofing agent is added to the secondary slurry.
[0011] In some optional embodiments, in the vacuum adsorption molding step, a custom mold is used, and the adsorption time is precisely controlled to be 8-15 seconds under a vacuum of -0.06 ~ -0.08 MPa.
[0012] In some optional embodiments, the hot-pressing drying and shaping step employs a multi-stage hot-pressing process; First stage: Temperature 130-150℃, pressure 1.5-2.0 MPa, hot pressing time 60-80 seconds; Second stage: Temperature 170-190℃, pressure 3.0-4.0 MPa, hot pressing time 40-60 seconds.
[0013] Thirdly, embodiments of this application provide a pulp molded article for food packaging, wherein the pulp molded article is prepared using the preparation method described in the above embodiments.
[0014] The pulp for food packaging molded products provided in this application embodiment can fundamentally and effectively reduce the internal porosity of the finished product, significantly improve its barrier properties, mechanical strength and moisture resistance, while ensuring that the final product maintains good biodegradability and environmental advantages, and the process itself should be industrially feasible and cost-effective, so as to promote the widespread application of pulp molding in the field of high-end food packaging. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0016] Figure 1 This is a schematic flowchart of an embodiment of the method for preparing pulp molded articles for food packaging according to this application; Figure 2 This is a schematic flowchart of an embodiment of the pulp preparation for food packaging molded articles. Detailed Implementation
[0017] The present application will now be described in further detail with reference to the accompanying drawings and embodiments. It should be particularly noted that the following embodiments are for illustrative purposes only and do not limit the scope of the application. Similarly, the following embodiments are only some, not all, embodiments of the present application, and all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of the present application.
[0018] The terms "first," "second," and "third" used in the embodiments of this application are for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first," "second," or "third" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified. All directional indications (such as up, down, left, right, front, back, etc.) in the embodiments of this application are only used to explain the relative positional relationships and movement of components in a specific posture (as shown in the figures). If the specific posture changes, the directional indication will also change accordingly. The terms "comprising" and "having," and any variations thereof, in the embodiments of this application are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or components inherent to these processes, methods, products, or devices.
[0019] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0020] First, this application provides a pulp for molded pulp products for food packaging. The pulp includes: 85-95 parts by weight of plant fiber pulp (based on a total solids mass of 100 parts by weight), specifically 85 parts by weight, 85.5 parts by weight, 86 parts by weight, 88 parts by weight, 90 parts by weight, 92 parts by weight, 95 parts by weight, etc.; 5-15 parts by weight of nanocellulose (based on a total solids mass of 100 parts by weight), specifically 5 parts by weight, 6 parts by weight, 6.5 parts by weight, 7 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, etc.; and 3-7 parts by weight of waterproofing agent, specifically 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, etc.
[0021] Optionally, the plant fiber pulp in this embodiment is selected from at least one of bamboo pulp, softwood pulp, hardwood pulp, sugarcane pulp, and wheat straw pulp. The matrix skeleton is formed by the combination of long and short fibers. Optionally, the plant fiber pulp in this embodiment includes a mixture of 40%-60% long fibers (such as softwood pulp, fiber length 1.5-2.5 mm) and 60%-40% short fibers (such as hardwood pulp or sugarcane pulp, fiber length 0.8-1.5 mm) to achieve the best balance between strength and formability. Among them, softwood pulp (NBKP): with long and coarse fibers, averaging 2.2-2.8 mm in length, it is the core reinforcing phase that forms a three-dimensional network skeleton and provides mechanical strength; hardwood pulp (LBKP): with short and fine fibers, averaging 0.8-1.2 mm in length, it has excellent flexibility and a large specific surface area, used to fill the gaps between long fibers and improve the uniformity and smoothness of the material; bamboo pulp: with fiber morphology between wood pulp and bamboo pulp, averaging 1.5-2.0 mm in length, it has both good strength and flexibility, and is a basic pulp with excellent comprehensive performance; sugarcane pulp: with the shortest fibers and a high content of impurities, averaging 0.5-1.0 mm in length, it has a large number of fine fiber components and low cost, mainly used to further fill pores and reduce costs, but its strength is poor when used alone.
[0022] The nanocellulose has an average diameter of 5-100 nm and an average length of 0.1-10 μm. Optionally, the nanocellulose may include any one or a combination of two of cellulose nanofibers (CNF) and cellulose nanocrystals (CNC). When used in combination, the network construction of CNF and the pore-filling effect of CNC may be utilized. Cellulose nanofibers have a diameter of 10-50 nm and a length of 1-5 μm; they exhibit a high aspect ratio network structure and can form strong hydrogen bonds and mechanical interlocks with plant fibers, making them the preferred choice for improving strength, toughness, and density.
[0023] Cellulose nanocrystals range from 5-30 nm in size and 0.1-0.5 μm in length. They exhibit a short, rod-shaped, rigid structure with high crystallinity, effectively filling finer pores. They significantly reduce air permeability and enhance barrier properties and rigidity, but their toughening effect is not as good as CNF.
[0024] Optionally, the waterproofing agent in this embodiment includes any one or a combination of multiple of alkyl ketene dimers, alkenyl succinic anhydride, and paraffin emulsions.
[0025] The pulp used in the food packaging pulp molding articles in this application embodiment has the following main advantages.
[0026] 1. High-efficiency filling and reinforcement: Utilizing the synergistic effect of nanoscale CNF and CNC, CNF forms a flexible network bridging fiber, while CNC acts as rigid particles to fill nanoscale pores, together significantly reducing porosity and simultaneously improving strength and barrier properties.
[0027] 2. Outstanding environmental friendliness: Using bio-based nanocellulose as the core reinforcing agent, the use of traditional non-degradable wet strength agents is greatly reduced or avoided, ensuring the product's fully degradable and environmentally friendly advantages.
[0028] 3. Performance can be designed: By adjusting the ratio of CNF to CNC, the total amount of nanocellulose added, and the fiber gradation of the base pulp, the performance of the final product can be flexibly controlled to meet the needs of different application scenarios.
[0029] 4. The process is feasible and economical: The optimal dosage range of key components has been identified (e.g., about 10 parts of nanocellulose). While ensuring a significant improvement in performance, the water permeability of the slurry and the production cost are also taken into account, making it a potential candidate for industrial-scale promotion.
[0030] In addition, this application also provides a method for preparing pulp molded articles for food packaging. Please refer to [link to relevant documentation]. Figure 1 , Figure 1 This is a schematic flowchart of an embodiment of the preparation method of pulp molded articles for food packaging according to this application. The preparation method includes, but is not limited to, the following steps.
[0031] Step S100: Prepare the slurry.
[0032] In this step, please refer to Figure 2 , Figure 2 This is a schematic flowchart of an embodiment of the pulp for preparing molded articles of pulp for food packaging, which includes the following steps.
[0033] In step S110, the plant fiber pulp board is decomposed in water to prepare a uniform primary pulp with a concentration of 1-5 wt%.
[0034] High-intensity dispersion using a hydraulic pulper is preferred to ensure complete fiber dissociation. Specifically, each pure pulp is dispersed for 15 minutes using a high-frequency descaling machine at 2000 rpm / min. Two or more pulps are mixed at a specific oven-dry mass ratio. The mixed pulp is then pulped in a high-concentration refiner at 1650 rpm, resulting in a final pulp concentration of 3 ± 0.5 wt% and a freeness of 35°SR.
[0035] In step S120, under high-speed shearing, nanocellulose is added to deionized water to prepare a stable suspension of 0.5-1.0 wt%, and the suspension is subjected to ultrasonic treatment.
[0036] Under high-speed shear (>5000 rpm), nanocellulose (CNF, CNC, or a mixture of both as needed) is slowly added to deionized water to prepare a stable suspension of 0.5-1.0 wt%. The suspension is then subjected to ultrasonic treatment (600W power, 15-20 minutes) to thoroughly disperse the nanofiber bundles and prevent aggregation.
[0037] Step S130: Add the nanocellulose suspension to the primary plant fiber slurry and stir to obtain the secondary slurry.
[0038] The treated nanocellulose suspension is slowly added to the primary slurry prepared in step S110 under stirring (300-500 rpm). Stirring continues for at least 30 minutes to ensure thorough mixing and adsorption of the nanocellulose and plant fibers. Metered-up process water is then added to form a secondary slurry with an overall concentration of 0.15-0.45 wt%. The amount of nanocellulose added is 5-10% of the total dry slurry mass concentration.
[0039] Step S140: Add the emulsified waterproofing agent to the secondary slurry.
[0040] The pre-emulsified waterproofing agent (such as AKD emulsion) is added to the above-mentioned secondary slurry mixture while stirring. The amount of waterproofing agent added is 3% of the total dry slurry mass concentration. After adding the waterproofing agent, the entire mixture is stirred for approximately 30 minutes. For specific slurry proportions, please refer to the phase description in the foregoing embodiments.
[0041] Please continue reading. Figure 1 In this embodiment, the preparation method of pulp molded products for food packaging also includes step S200, vacuum adsorption molding.
[0042] In step S200, a custom mold is used, and the slurry suction time is precisely controlled to be 8-15 seconds under a vacuum of -0.06 ~ -0.08 MPa. This combination of parameters is designed to ensure that the slurry uniformly covers the mold, forming a dense and uniformly thick wet blank, while avoiding structural delamination or loss of nanocellulose due to excessively rapid slurry suction.
[0043] Step S300: Hot pressing, drying, and shaping.
[0044] In this step, a multi-stage hot-pressing process can be used to simultaneously achieve efficient drying, pore densification, and curing of the waterproofing agent.
[0045] Phase 1 (Pre-curing and Moisture Migration): Temperature 130-150℃, Pressure 1.5-2.0 MPa, Hot-pressing time 60-80 seconds. The main task of this phase is to remove most of the free water and to initially position flexible components such as CNF.
[0046] The second stage (deep curing and densification): temperature 170-190℃, pressure 3.0-4.0 MPa, hot pressing time 40-60 seconds. In this stage, the higher temperature and pressure promote the formation of more hydrogen bonds between fibers, CNC fully fills the nanopores, and the waterproofing agent is completely cured, ultimately achieving the comprehensive performance of low porosity, high strength, and excellent barrier properties in the product.
[0047] The pulp molded products for food packaging obtained by the preparation method in this embodiment can be used for food packaging boxes, lunch boxes or trays.
[0048] In one specific embodiment, the following parameters are used.
[0049] Slurry preparation: Each pure slurry was dispersed for 15 minutes using a high-frequency descaling machine at a speed of 2000 rpm / min. Two or more slurries were mixed at a specific oven-dry mass ratio. The mixed slurry was then pulped in a high-concentration refiner at a speed of 1650 rpm. The final pulping concentration was 3 ± 0.5 wt%, and the degree of freeness was 35°SR. Nanocellulose addition steps: Under high-speed shear (10000 rpm), nanocellulose (CNF, CNC, or a mixture of both as needed) is slowly added to deionized water to prepare a stable suspension of 0.5 wt%. The suspension is then ultrasonically treated (600W power, 15 minutes) to thoroughly disperse the nanofiber bundles and prevent agglomeration. The treated nanocellulose suspension is then slowly added to the prepared primary slurry while stirring (400 rpm). The amount of nanocellulose added is 5-10% of the total dry slurry mass concentration. Stirring is continued for at least 30 minutes to ensure that the nanocellulose and plant fibers are fully mixed and adsorbed. The metered process water is then added to finally form a slurry with a total concentration of 0.3±0.02wt%. Add waterproofing agent to the slurry at a concentration of 3% of the total dry slurry mass, and stir the mixture for 30 minutes. The vacuum adsorption molding process was adopted, with a vacuum degree of -0.07MPa and an adsorption time of 10s.
[0050] The temperature, pressure, and drying time of the hot pressing depend on the specific implementation.
[0051] The thermal conductivity parameters of the examples and comparative examples are compared as follows.
[0052]
[0053] The performance evaluation method is as follows.
[0054] Moisture content Test standard: GB / T 462-2023 "Determination of moisture content in analytical samples of paper, paperboard and pulp" Testing instrument: Electronic balance (accuracy 0.001g) Test method: Weigh an appropriate amount of pulp molding sample (m1) using an electronic balance with an accuracy of 0.001g. Then, place the sample in a constant temperature drying oven at 105℃ to dry to constant weight. After taking it out, immediately place it in a desiccator to cool to room temperature and weigh it again (m2). The moisture content (W) of the sample is calculated using the following formula: W = [(m1- m2) / m1] × 100%, with the result accurate to 0.1%.
[0055] compressive strength Test standard: GB / T 36787-2018 "Molded Pulp Tableware" - Test specifications for compressive strength. Testing instruments: Universal testing machine or dedicated compression tester Test Method: The conditioned sample is placed at the center of the lower pressure plate of the compression tester. The dimensions of the upper and lower pressure plates are no less than 100mm × 100mm, and the parallelism deviation is no greater than 1:2000. Pressure is applied to the sample at a rate of 12.5mm / min ± 2.5mm / min until it collapses. The maximum pressure value is recorded and accurate to 1N. For each sample, 5 valid samples with the rim facing upwards and 5 samples with the rim facing downwards are tested. The final result is expressed as the arithmetic mean of the compressive strength test values of 10 samples, in Newtons (N), rounded to the nearest integer. This indicator simulates the packaging's ability to withstand vertical pressure during stacking and transportation, and is a core mechanical performance characteristic for evaluating its feasibility as load-bearing packaging.
[0056] Tensile strength Test standard: GB / T12914 "Determination of tensile strength of paper and paperboard" Testing instrument: Horizontal tensile tester Test Method: During testing, a strip specimen, 15 mm wide and at least 230 mm long, should be cut from a flat area of the molded pulp product. After adjusting the specimen to a standard temperature and humidity environment, it should be vertically clamped into the upper and lower clamps of a horizontal tensile testing instrument, ensuring that the effective gauge length of the specimen is 180 mm after clamping. Then, a constant tensile test is performed at a speed of 20 mm / min until the specimen breaks. The instrument will automatically record the maximum force at break, and the tensile strength (kN / m) of the specimen can be calculated.
[0057] Bursting Index Test standard: GB / T 454-2002 "Determination of bursting strength of paper" Testing instrument: Mullen bursting strength tester Test method: Cut a sample with a size of not less than 70mm × 70mm from a flat part of the sample and clamp it tightly between the two clamping rings of the bursting strength tester. The upper clamping ring is made of transparent material for easy observation. Start the instrument and apply gradually increasing pressure to the sample with glycerin or hydraulic oil at a constant rate until the sample breaks. Record the maximum pressure value at this time, which is the bursting strength, in kilopascals (kPa). The bursting strength index is calculated by dividing the measured bursting strength value by the sample's quantity (mass per unit area), in kilopascals·m² / g. The final result is the arithmetic mean of the test values of at least ten valid samples.
[0058] Breathability Test standard: ISO 5636-5:2013 "Determination of air permeability of paper and paperboard" Testing instrument: Glycol air permeability meter Test method: The sample is held flat on the instrument's ring clamp to completely seal the test area with a diameter of 2.5 inches. Then, the standard weight piston in the instrument's pressure cylinder is released, allowing it to fall at a constant speed under gravity. The time required for 100 ml of air to completely permeate the sample is recorded. This time value is the Grylls permeability, measured in seconds.
[0059] Cobb value (water absorption value) Test standard: GB / T 1540 "Determination of water absorbency of paper and paperboard (Cobb method)" Testing instrument: Cobb absorbance meter Test Method: Press the sample firmly into the instrument, add a specified amount of water, ensuring the test area (100 cm²) is in contact with the water surface. After a specific contact time (60 seconds in this experiment), pour off the water, blot dry any remaining moisture with absorbent paper, and immediately weigh the absorbed mass. The water absorption value is expressed as the mass of water absorbed per unit area of the sample (g / m²). This indicator directly reflects the material's moisture-proof performance and resistance to liquid penetration, and is crucial for packaging foods containing water or oil.
[0060] Water contact angle Test Standard: GB / T 30693-2014 Test Instruments: Testing instrument: Contact angle measuring instrument Test method: Under standard laboratory conditions, the sample is fixed flat on the sample stage. A drop of distilled water (volume 2.0 μL) is dropped vertically onto the sample surface using a microsyringe. The image of the water droplet is captured in real time by the instrument's camera. At 5 seconds after the water droplet contacts the surface, the static water contact angle is calculated by the instrument software using the angle measurement method. Each sample is tested at least five different locations. The results are expressed as an average value in degrees (°).
[0061] Microbial degradation Testing Standard: GB / T 39951-2021 "Evaluation Method for Degradability Performance of Disposable Paper Products" Testing instrument: Laboratory simulated composting degradation testing system Test Methods and Extensions: A sample with a known dry weight (M0, g) was mixed with mature compost inoculum and placed in a temperature-controlled reactor at 58±2℃. The biodegradability of the material was calculated by precisely monitoring the amount of carbon dioxide (CO2) produced during the test period (e.g., 45 days or up to 6 months) using gas chromatography and comparing it with a blank control group (containing only inoculum).
[0062] Among them, the cumulative theoretical CO2 production is: Total(CO2)=M*(TOC / 100)*(44 / 12) M represents the sample with known dry weight; TOC represents the total organic carbon content of the sample (%); 44 is the molecular weight of CO2; 12 is the atomic weight of carbon (C). Time(CO2) = [ (CO2(sample) - CO2(blank)) / Total(CO2)] × 100% CO2(sample) represents the cumulative amount of CO2 (g) released by the sample group at time t; CO2(blank) represents the cumulative amount of CO2 (g) released by the blank group at time t.
[0063] When the calculated final biodegradability rate is not less than 60%, the sample can be deemed to have passed the biodegradation test. This is the ultimate test to verify the final biodegradability and environmental properties of the material, ensuring that it can return to nature under specific waste disposal conditions, which is in line with the core concept of green packaging.
[0064] By comprehensively characterizing the above indicators, we can systematically and deeply evaluate the combined effects of nanocellulose modification on pulp molding materials in terms of structure, mechanics, barrier properties, and environmental behavior, providing solid data support for product development, quality control, and market application.
[0065] The performance test results of the examples and comparative examples are shown in the table below.
[0066]
[0067] The performance test data system reveals the synergistic reinforcement mechanism and structure-property relationship of nanocellulose and plant fiber gradation in pulp molding materials.
[0068] 1. Verification of the synergistic enhancement mechanism and nanoscale effect of nanocellulose Comparing Comparative Example 1 (blank control) with Example 1 (CNF reinforcement) and Example 2 (CNC filling), it is evident that adding only a single type of nanocellulose can significantly improve the material's mechanical strength (e.g., compressive strength increased from 1.35 kN to over 2.30 kN) and barrier properties (air permeability increased from ≤100 s to over 380 s). However, the key discovery of this invention lies in the synergistic effect exhibited by Example 3 (synergistic compounding). This example not only demonstrates superior compressive strength (2.45 kN) and burst strength index (6.10 kPa·m² / g) compared to the single-component system, but also possesses excellent overall barrier properties (air permeability 980 s). This "rigid-flexible" effect can be attributed to: CNF forming a flexible three-dimensional network framework, which, through strong hydrogen bonding and mechanical interlocking with plant fibers, bears the main stress, effectively improving the material's toughness and strength; while CNC, as rigid nanoparticles, focuses on filling the micro-nano pores formed by the CNF network, thereby enhancing the material's density and barrier properties to an even higher level. Furthermore, the results of Comparative Example 2 (microcrystalline cellulose, MCC) provide evidence for its irreplaceable nature at the nanoscale. Its properties are inferior to any of the nanocrystalline cellulose examples, demonstrating that high specific surface area and strong interfacial bonding at the nanoscale are key conditions for achieving the technical effects of this invention.
[0069] 2. Realization of fiber gradation and performance designability The technical solutions of this invention exhibit excellent performance designability. Example 6 (high-strength design, high long fiber ratio) achieves optimal mechanical properties (compressive strength 2.60 kN) by constructing a robust fiber skeleton primarily composed of softwood pulp, which works synergistically with nanocellulose, making it suitable for high-strength applications. For Examples 4 (bamboo pulp application) and 7 (economical design), the wood / bamboo / sugarcane composite pulp maintains excellent performance while optimizing specific product properties (such as surface smoothness) or economic efficiency by introducing specialty non-wood pulps or low-cost pulps. This demonstrates that by adjusting the gradation of plant fibers, this invention can flexibly adapt to different market demands.
[0070] 3. Optimization of key component addition amount and process economy From an industrialization perspective, the comparison between Example 8 (low addition, 5 parts), Example 1 (10 parts), and Example 10 (high addition, 15 parts) clarifies the performance-cost relationship. As the CNF addition increases from 5 parts to 10 parts, the material performance is significantly improved; however, when the addition continues to increase to 15 parts, the marginal benefit of performance improvement decreases, and it may negatively impact the slurry's water permeability. Therefore, in the technical solution of this patent, an addition of 10 parts of nanocellulose is a technical choice that achieves a good balance between performance improvement, process feasibility, and production cost, laying a foundation for the industrial promotion of this invention.
[0071] 4. The advantages of fully degradable and environmentally friendly technology become apparent. The embodiments of this invention demonstrate excellent performance while maintaining a biodegradability rate of over 83%, meeting the requirements for fully degradable and environmentally friendly materials. Comparative Example 3 (without waterproofing agent) provides a strong contrast: although this group exhibits the highest biodegradability rate (95%), its waterproofing is poor (Cobb value ≥ 100 g / m²), failing to meet the basic requirements for packaging materials. This comparison fully demonstrates that this invention, through the use of fully bio-based nanocellulose for bulk reinforcement and supplemented with an appropriate amount of biodegradable waterproofing agent, ensures the biodegradability of the product without sacrificing performance, avoiding the environmental burden caused by relying on non-degradable chemical additives in traditional technologies.
[0072] Conclusion: In summary, the technical solution of this invention, by precisely utilizing the synergistic reinforcing effect of different types of nanocellulose and combining it with an optimized plant fiber gradation system, has successfully developed a pulp molding material that possesses high strength, high barrier properties, and full degradability, while also exhibiting excellent industrialization potential. This solution effectively solves the technical challenges of insufficient strength and barrier properties in traditional pulp molding products, as well as the difficulty in simultaneously achieving high performance and full degradability, providing a clear and feasible technical path for replacing traditional plastic packaging.
[0073] The method for preparing pulp molded articles for food packaging in this application embodiment has the following technical effects.
[0074] 1. Effectively improves the performance deficiencies of traditional pulp molding products caused by their porous structure. In existing technologies, methods that rely solely on increasing hot-pressing pressure or beating degree to reduce porosity have limited effectiveness and can easily damage fibers or affect production. This invention, by adding nanocellulose, utilizes its tiny size to effectively penetrate the gaps between plant fibers, acting as a "filler" and "bridge." This method more gently and effectively reduces the porosity of the finished product, making it denser and naturally improving compressive strength, barrier properties, and moisture resistance.
[0075] 2. While improving performance, the material's environmentally friendly and biodegradable properties are well maintained. To improve performance, common practices include adding non-biodegradable chemical additives (such as wet strength agents) or covering with a plastic film, but this can affect the recycling and degradation of the pulp molding process. This invention primarily utilizes nanocellulose (which itself comes from natural plants) for reinforcement, reducing or avoiding reliance on non-environmentally friendly additives. Products made in this way can still degrade and be recycled normally after use, meeting the fundamental requirements of green packaging.
[0076] 3. By combining nanocellulose with different properties, the product's performance becomes more balanced and outstanding. Long, flexible cellulose nanofibers (CNFs), resembling noodles, effectively connect fibers and enhance toughness; while rigid cellulose nanocrystals (CNCs), like short sticks, excel at blocking tiny pores and improving barrier properties. Mixing the two in a specific ratio allows for the synergistic effect of their respective strengths, resulting in a material that is both strong and dense, effectively solving the previous challenge of simultaneously improving both strength and barrier properties.
[0077] 4. A feasible and cost-controllable technical solution is provided for actual production. This invention does not aim to improve a single performance metric, but rather comprehensively considers production feasibility and cost. A relatively economical and effective addition amount of nanocellulose was determined, which can significantly improve performance without excessively increasing costs or making the production process difficult. Simultaneously, by rationally combining different types and costs of plant fibers (such as using some inexpensive sugarcane pulp), raw material costs can be further controlled while ensuring core performance, making the technology more easily accepted and promoted by the industry.
[0078] The key technologies and parameters that produce the most direct effect of this preparation method are not limited to the following points.
[0079] 1. The rigid-flexible composite type and synergistic parameters of nanocellulose This invention employs a blend of cellulose nanofibers (CNF) and cellulose nanocrystals (CNC). The high aspect ratio CNF (10-50 nm in diameter, 1-5 μm in length) acts as a flexible three-dimensional network framework, effectively bearing and transferring stress, and is the primary source of the material's toughness and strength. Meanwhile, the short rod-shaped CNC (5-30 nm in diameter, 0.1-0.5 μm in length) acts as rigid nanoparticles, focusing on filling nanoscale pores, and is key to improving the material's density and barrier properties. Experimental results show that when the two are blended at a CNF:CNC mass ratio of (1:1) and the total addition is controlled within the range of 5 to 15 parts by weight, a significant synergistic effect of "rigidity and flexibility" is exhibited. Specifically, when the total addition is 10 parts by weight, the optimal balance is achieved between performance, processing, and cost, simultaneously optimizing the material's compressive strength and barrier properties.
[0080] 2. The optimal economical addition amount of nanocellulose The amount of nanocellulose added is a key parameter for balancing performance, processing, and cost. Data from the examples clearly show that 10 parts by weight (relative to 100 parts by weight of plant fiber pulp) is a critical performance and economic inflection point. At this addition amount (as in Examples 1, 3, and 4), material properties are significantly improved while maintaining good drainage and formability of the pulp. When the addition amount is reduced to 5 parts by weight (Example 8), the performance improvement is limited; and when the addition amount is further increased to 15 parts by weight (Example 10), the marginal benefit of performance improvement decreases, and it negatively impacts the drainage of the pulp. In this patented technical solution, 10 parts by weight is an economically viable addition amount with industrial-scale promotion value.
[0081] 3. Optimized gradation scheme of plant fiber matrix The gradation of plant fiber pulp is the fundamental platform for the reinforcing effect of nanocellulose. The optimal gradation scheme determined in this invention is a composite matrix consisting of 40%-60% long fibers (such as softwood pulp, fiber length 1.5-2.5 mm) and 60%-40% short fibers (such as hardwood pulp, bamboo pulp, or sugarcane pulp, fiber length 0.8-1.5 mm). Example 6 (long fiber: short fiber = 5:5) exhibits excellent structural strength, while Examples 4, 5, and 7 demonstrate the flexibility to achieve specific performance or cost targets by adjusting the proportion of non-wood pulp. This optimized gradation system, in synergy with the nanocellulose reinforcement, jointly determines the high performance and controllable cost structure of the final product.
[0082] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a process method (including pulp ratio and preparation parameter adjustment) for reducing porosity in pulp molding for food packaging. This invention achieves the above objective by adding nanocellulose of specific morphology and size to pulp fibers as a highly efficient pore filler and reinforcing agent, combined with an optimized molding process. Nanocellulose can deeply fill the micron- and nano-scale pores in the pulp fiber network and form strong hydrogen bonds with the pulp fibers through its huge specific surface area, thereby improving the density, mechanical strength, and barrier properties of the product without relying on or with reduced reliance on non-environmentally friendly chemical additives. Firstly, this invention provides a nanocellulose composite pulp molding system that fundamentally reduces the intrinsic porosity of the finished product by using specifically selected nanocellulose as a pore filler and reinforcing agent. Secondly, it optimizes the pulp ratio and molding process parameters to ensure that the nanocellulose fully fills the pores between pulp fibers, forming a dense network structure. Thirdly, it significantly improves the barrier properties and mechanical strength of pulp molded products while maintaining good biodegradability and environmental advantages. Finally, it provides an industrially feasible and cost-effective preparation method, promoting the widespread application of pulp molding in the high-end food packaging field.
[0083] The above description is only a part of the embodiments of this application and does not limit the scope of protection of this application. Any equivalent device or equivalent process transformation made based on the content of this application specification and drawings, or direct or indirect application in other related technical fields, are similarly included in the patent protection scope of this application.
Claims
1. A pulp for molded paper products used in food packaging, characterized in that, The pulp comprises: 85-95 parts by weight of plant fiber pulp, 5-15 parts by weight of nanocellulose, and 3-7 parts by weight of waterproofing agent.
2. The slurry according to claim 1, characterized in that, The nanocellulose includes any one or a combination of two of cellulose nanofibers and cellulose nanocrystals.
3. The slurry according to claim 1, characterized in that, The nanocellulose has an average diameter of 5-100 nm and an average length of 0.1-10 μm.
4. The slurry according to claim 1, characterized in that, The waterproofing agent includes any one or a combination of multiple of alkyl ketene dimers, alkenyl succinic anhydride, and paraffin emulsions.
5. The slurry according to claim 2, characterized in that, The nanocellulose includes cellulose nanofibers and cellulose nanocrystals. The cellulose nanofibers have a diameter of 10-50 nm and a length of 1-5 μm. The cellulose nanocrystals have a diameter of 5-30 nm and a length of 0.1-0.5 μm.
6. A method for preparing pulp molded articles for food packaging, characterized in that, The preparation method includes: Prepare a slurry, wherein the slurry is the slurry according to any one of claims 1-5; Vacuum adsorption molding; Hot pressing, drying, and shaping.
7. The preparation method according to claim 6, characterized in that, The steps for preparing the slurry include: Plant fiber pulp boards are decomposed in water to prepare a uniform primary pulp with a concentration of 1-5 wt%. Under high-speed shearing, nanocellulose was added to deionized water to prepare a stable suspension of 0.5-1.0 wt%, and the suspension was then subjected to ultrasonic treatment. The nanocellulose suspension was added to the primary plant fiber pulp and stirred to obtain the secondary pulp; The emulsified waterproofing agent is added to the secondary slurry.
8. The preparation method according to claim 6, characterized in that, In the vacuum adsorption molding step, a custom mold is used, and the adsorption time is precisely controlled to be 8-15 seconds under a vacuum of -0.06 ~ -0.08 MPa.
9. The preparation method according to claim 6, characterized in that, The hot-pressing drying and shaping step adopts a multi-stage hot-pressing process; First stage: Temperature 130-150℃, pressure 1.5-2.0 MPa, hot pressing time 60-80 seconds; Second stage: Temperature 170-190℃, pressure 3.0-4.0 MPa, hot pressing time 40-60 seconds.
10. A pulp molded product for food packaging, characterized in that, The pulp molded article is prepared by the preparation method according to any one of claims 6-9.